Pengaruh Kualitas Pelayanan Dekranasda Kota Probolinggo Terhadap Loyalitas Masyarakat Pada Produk Lokal Dengan Kepuasan Konsumen Sebagai Intervening - Lailatul Fitria, Nurul Jannah (Jurnal Administrasi Karya Dharma, 2023)
The quality of public services needs to be improved in order to provide quality services for local communities. The latest issue that requires the role of government in public services is related to managing local resources and potential and providing media in developing MSMEs in the field of local product sales. As in Probolinggo City, public services by accommodating the needs of local products are carried out by Dekranasda Kota Probolinggo as a partner. Dekranasda Kota Probolinggo does not only carry out services to MSME groups with empowerment, mentoring, and others. However, the implementation of public services is also carried out by providing an outlet to help market local products and the community get the needs of local products typical of Probolinggo City. This attracted researchers in conducting deeper research.  The purpose is to determine the effect of Public Service Quality on Customer Satisfaction; to determine the effect of Customer Satisfaction on community loyalty; to determine the effect of Service Quality on Community Loyalty; to determine the mediating effect of Customer Satisfaction on the effect of Service Quality on Community Loyalty. The population in this research is the entire community as consumers or visitors to the Probolinggo City Dekranasda Outlet. The sample uses the Purposive Sampling method with a total of 100 respondents with the criteria of the community as consumers who buy products at least 2 times within 3 months. Retrieval. Data collection techniques using a questionnaire. Data analysis using Path Analysis. The research can be concluded that Public Service Quality affects Consumer Satisfaction; Consumer Satisfaction affects Community Loyalty; Public Service Quality affects Community Loyalty; customer satisfaction is able to mediate the effect of public service quality on consumer loyalty